Diabetes Self-Management and Leptin in Mexican Americans With Type 2 Diabetes: The Starr County Border Health Initiative. (November 2013) - Brown, Sharon A.; Kouzekanani, Kamiar; García, Alexandra A.; Orlander, Philip R.; Hanis, Craig L.
Purpose: The purpose of the study was to (1) characterize leptin in Mexican Americans with poorly controlled type 2 diabetes, (2) examine relationships among leptin and indicators of diabetes status (body mass index and A1C), and (3) explore the effects of a culturally tailored diabetes self-management education intervention on leptin. Methods: In Starr County, an impoverished Texas-Mexico border community, 252 Mexican Americans with type 2 diabetes were recruited to test a diabetes self-management education intervention culturally tailored in terms of language, dietary recommendations, social emphasis, family participation, and incorporation of cultural health beliefs. Groups of 8 participants were randomized to experimental or wait-listed control conditions. Outcomes were measured at 3, 6, and 12 months; by 12 months, 109 had complete leptin data. Results: Most participants were women and, on average, 55 years of age, diagnosed with diabetes for 8 years, obese, and in poor glycemic control. Three variables—body mass index, sex, A1C—explained 36% of the variance in baseline leptin; there were no intervention effects on leptin. Sex, time, and gender × time interaction effects on leptin were statistically significant; greater increases in leptin over time occurred in women compared to men. In women, fasting blood glucose changes from baseline to 12 months significantly predicted leptin changes from baseline to 12 months; in men, body mass index changes predicted leptin change. Conclusions: With increasing obesity rates, further research is warranted to determine if leptin is a useful intervention target in type 2 diabetes.